The Effect of Moringa Oleifera. Lam Leaf Extract on Bcl2 and Bax Expression in Paracetamol-induced Renal Tubular Apoptosis in Rats - Jannah, Miftahul; Subagyo, Djoko Trihadi Lukmono; Nasihun, Taufiqurrachman (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
BACKGROUND: Paracetamol may cause apoptosis in the renal tubules. Moringa leaf (Moringa oleifera. Lam) has been shown to have antioxidant effects due to its f lavonoids. In addition, f lavonoids also have biological effects to modulate the signal-transduction pathway.OBJECTIVE: to investigate the effect of Moringa oleifera Lam extract on Bcl-2 and Bax expression on paracetamol-induced renal tubular injury.METHODS: in this post-test only control group design study, 24 rats were divided into 4 groups: AqC-G (aquades), EtC-G (70% ethanol), MoL1-Gand MoL2-G (moringa leaf extract at the dose of 1.075 g/Kg BW and 2.150 g/Kg BW respectively). Expression of Bcl2 and Bax was determined using immunohistochemical staining. The data on the number of Bcl2 and Bax expressions tested with One Way Anova followed by the Post Hoc LSD test.RESULTS: Post Hoc LSD test showed that the expression of Bcl-2 in the experimental groups ((MoL1-G (9.1) and MoL2-G (13,683)) was significantly higher compared to that of controls (p<0.001). Bax expression in the experimental groups (MoL1-G (6,85) and MoL2-G (2,633)) was significantly lower compared to that of controls, p <0.001.CONCLUSION: The administration of Moringa leaf extract at the dose of 1,075 and 2,150 increases Bcl-2 expression and decreases Bax expression in paracetamol-induced renal tubular injury.